Evaluation of the Clinical and Antimicrobial Effects of the Er:YAG Laser or Topical Gaseous Ozone as Adjuncts to Initial Periodontal Therapy - KADİR, TANJU (MARY ANN LIEBERT INC, 2013)
Objective: The aim of this study was to evaluate the clinical and microbiological results of treatment with the Er:YAG laser and topical gaseous ozone application as adjuncts to initial periodontal therapy in chronic periodontitis (CP) patients. Background data: Although many studies have evaluated the effectiveness of the Er:YAG laser as an adjunct to initial periodontal therapy, few studies have focused on the use of gaseous ozone as an adjunct. Materials and methods: Thirty patients with CP were randomly divided into three parallel groups, each composed of 10 individuals with at least four teeth having at least one approximal site with a probing depth (PD) of >= 5mm and a sulcus bleeding index (SBI) >= 2 in each quadrant. Groups of patients received: (1) Scaling and root planing (SRP) + Er:YAG laser; (2) SRP + topical gaseous ozone; or (3) SRP alone. The microbiological and clinical parameters were monitored at day 0 and day 90. Results: At the end of the observation period, statistically significant improvements in clinical parameters were observed within each group. Parallel to the clinical changes, all treatments reduced the number of total bacteria and the proportion of obligately anaerobic microorganisms. Although intergroup comparisons of microbiological parameters showed no significant differences, clinical findings, including attachment gain and PD reduction, were found to be statistically significant in favor of the SRP + Er:YAG laser group. Conclusions: Although statistically nonsignificant, the fact that the obligate anaerobic change was mostly observed in the SRP+ Er:YAG laser group, and a similar decrease was noted in the SRP + topical gaseous ozone group, shows that ozone has an antimicrobial effect equivalent to that of the Er:YAG laser.
Keywords: ER-YAG LASER; 2-YEAR FOLLOW-UP; SPLIT-MOUTH; METRONIDAZOLE; DEBRIDEMENT; GINGIVITIS